2011
DOI: 10.1143/apex.4.124101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AlGaN Back Barrier on AlN/GaN-on-Silicon High-Electron-Mobility Transistors

Abstract: In this work, the effects of an AlGaN back barrier in the dc and RF performances of AlN/GaN high-electron-mobility transistors (HEMTs) grown on 100 mm Si substrates have been investigated. It is shown that the outstanding dc performance in highly scaled AlN/GaN-on-Si HEMTs can be fully preserved when introducing an AlGaN back barrier while significantly reducing the sub-threshold drain leakage current and enhancing the RF performance by the reduction of short-channel effects. Therefore, the AlN/GaN/AlGaN doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 18 publications
0
45
0
1
Order By: Relevance
“…Recently, we have developed in this frame a novel technology based on an AlN/GaN/AlGaN-on-Si double heterostructure. It was demonstrated that a low leakage current, a high transconductance, and an extremely high current density can be achieved simultaneously using this double heterostructure [1][2][3][4][5]. Furthermore, as can be seen in Fig.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, we have developed in this frame a novel technology based on an AlN/GaN/AlGaN-on-Si double heterostructure. It was demonstrated that a low leakage current, a high transconductance, and an extremely high current density can be achieved simultaneously using this double heterostructure [1][2][3][4][5]. Furthermore, as can be seen in Fig.…”
Section: Introductionmentioning
confidence: 76%
“…current [7,8]. On top of the material quality, the in situ grown SiN cap layer has been a key feature for controlling the surface parasitic leakage current and achieving high performance [9][10][11], namely by preventing the strain relaxation of the barrier layer. In this paper, we report on the high breakdown voltage in highly scaled GaN transistors grown on a silicon substrate, showing that all the above-mentioned issues can be overcome in these emerging types of devices.…”
Section: Methodsmentioning
confidence: 99%
“…In this frame, we have demonstrated the possibility of preventing gate tunneling through highly scaled Aluminum Nitride (AlN) barrier thickness (below 5 nm) by showing an extremely low gate leakage current [7,8]. On top of the material quality, the in situ grown SiN cap layer has been a key feature for controlling the surface parasitic leakage current and achieving high performance [9][10][11], namely by preventing the strain relaxation of the barrier layer.…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому в последние 5 лет интенсивное раз-витие получило третье из упомянутых выше тех-нологических направлений создания нитридных гетероструктур -разработка структур на подложке кремния [3][4][5][6][7]. Применение Si в качестве подложеч-ного материала рассматривается как чрезвычайно перспективное направление в силу того, что потен-циал данной технологии гетероструктур GaN/Si обе-спечивается следующими факторами:…”
Section: направления развития производства гетероструктурunclassified